High Frequency of Specific Polysaccharide Antibody Deficiency in Adults With Unexplained, Recurrent and/or Severe Infections With Encapsulated Bacteria. (26th October 2022) - Stabler, Sarah; Lamblin, Catherine; Gaillard, Sacha; Just, Nicolas; Mihailescu, Mirela; Viget, Nathalie; Sy Ndiaye, Thierno; Dzeing Ella, Arnaud; Brunin, Guillaume; Weyrich, Pierre; Prevotat, Anne; Chenivesse, Cécile; et al.
Abstract: Background: Primary immunodeficiencies (PIDs) in adults are mainly revealed by recurrent and/or severe bacterial infections. The objective of this study was to evaluate a systematic research strategy of PIDs in adults with unexplained bacterial infections, with a special focus on specific polysaccharide antibody deficiency (SPAD). Methods: In this prospective multicenter study, inclusion criteria were recurrent benign upper and lower respiratory tract infections (RTIs) for at least two years (group 1), at least one upper or lower RTI requiring hospitalization (group 2), and/or at least one invasive infection documented with encapsulated bacteria (group 3). Main exclusion criteria were all local and general conditions that could explain infections. If no PID diagnosis was made, response to polysaccharide antigens was assessed using a pneumococcal polysaccharide vaccine. Results: From March 2015 to March 2020, 118 patients were included (37 males, median age of 41 years): 73, 17, and 28 in groups 1, 2, and 3, respectively. Forty-seven PIDs were diagnosed, giving an estimated frequency of 39.8% (95% confidence interval [CI] [30.4, 48.8]). SPAD was the most frequent diagnosis by far (n = 37/47, 78.7%), and was made in 23, 5, and 9 patients from groups 1 to 3, respectively. All SPAD patients received conjugate vaccines and, according to their infectious history, were on surveillance or treated with preventive antibiotics (n = 6) and/or with immunoglobulins replacement therapy (n = 10), the latter being dramatically efficient in all cases. Conclusions: Considering its high prevalence among adults with unexplained recurrent and/or severe bacterial infections, SPAD should be screened in those patients. Clinical Trials Registration: NCT02972281. Abstract : Primary immunodeficiencies (PIDs) revealed with encapsulated bacteria related infections. After ruling out favoring conditions, a systematic search for PIDs allows 40% of PIDs diagnoses. Specific anti-polysaccharide deficiency seems to a frequent diagnose in this selected population.